2019
DOI: 10.1177/1740774519858914
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a clinical trial using previous trials as historical control

Abstract: Background/Aims For single arm trials, a treatment is evaluated by comparing an outcome estimate to historically reported outcome estimates. Such a historically controlled trial is often analyzed as if the estimates from previous trials were known without variation and there is no trial-to-trial variation in their estimands. We develop a test of treatment efficacy and sample size calculation for historically controlled trials that considers these sources of variation. Methods We fit a Bayesian hierarchical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…One limitation of our study is that this is a single-arm trial, and therefore, the grade of evidence is not as high as that obtained from a randomized controlled trial 33 ; however, childhood APL is very rare, 34 and the excellent efficacy of arsenic plus ATRA for adult patients with APL has been well-confirmed. This is why our study was designed to be a single-arm trial in children with APL as recommended by experts in our clinical epidemiology and evidence-based medicine center.…”
Section: Discussionmentioning
confidence: 87%
“…One limitation of our study is that this is a single-arm trial, and therefore, the grade of evidence is not as high as that obtained from a randomized controlled trial 33 ; however, childhood APL is very rare, 34 and the excellent efficacy of arsenic plus ATRA for adult patients with APL has been well-confirmed. This is why our study was designed to be a single-arm trial in children with APL as recommended by experts in our clinical epidemiology and evidence-based medicine center.…”
Section: Discussionmentioning
confidence: 87%
“…Schoenfeld et al 94 . used a Bayesian hierarchical model to examine and compare the total sample sizes needed using historical vs. concurrent controls in the setting of trials of amyotrophic lateral sclerosis.…”
Section: Current Statistical Methods For Combining Current Controls Amentioning
confidence: 99%
“…93 Cuff also demonstrated through simulations that either standard or more conservative weighting of historical data may reduce power compared with ignoring historical data. 92 Schoenfeld et al 94 used a Bayesian hierarchical model to examine and compare the total sample sizes needed using historical vs. concurrent controls in the setting of trials of amyotrophic lateral sclerosis. They found that using only historical controls did not offer an advantage in total sample size over a two-armed RCT when accounting for between-trial heterogeneity.…”
Section: Reviewmentioning
confidence: 99%
“…The process of borrowing external data uses various Bayesian approaches that primarily differ in the assumptions regarding the relevance and exchangeability of the external data with the current trial [ 3 – 5 ]. They typically use power priors, down-weighting controls using fixed weights [ 3 , 6 ], or more complex meta-analytic priors such as normalized power prior [ 7 ], commensurate priors [ 4 ], robust meta analytic-predictive priors (MAP) [ 8 , 9 ], and supervised methods that manually adjust the informativeness of the prior based on measures of conflict between the prior information and the new trial data, assessed at the time of the analysis. Such a variety of proposed approaches was illustrated in a review that identified 58 Bayesian and 44 frequentist methods for incorporating historical data into a contemporary trial based on 52 articles [ 10 ].…”
Section: Introductionmentioning
confidence: 99%